2022
DOI: 10.1038/s41598-022-06836-x
|View full text |Cite
|
Sign up to set email alerts
|

Two new Russula species (fungi) from dry dipterocarp forest in Thailand suggest niche specialization to this habitat type

Abstract: Dry dipterocarp forests are among the most common habitat types in Thailand. Russulaceae are known as common ectomycorrhizal symbionts of Dipterocarpaceae trees in this type of habitat. The present study aims to identify collections of Russula subsection Amoeninae Buyck from dry dipterocarp forests in Thailand. A multi-locus phylogenetic analysis placed Thai Amoeninae collections in two novel lineages, and they are described here as R. bellissima sp. nov. and R. luteonana sp. nov. The closest identified relati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The suprapellis and subpellis are also thinner than the type material. However, the species can easily be recognized based on small to medium sized pileus with red colour, a smooth to purinose pileus surface, inamyloid suprahilar spots, basidiospore ornamentations that are composed of spines or warts connected by ne lines, and with hymenial cystidia and pileocystidia absent (Wisitrassameewong et al 2022). Russula bellissima is morphologically and phylogenetically closely related to the R. intervenosa reported from India and frequently grows in association with Shorea robusta dominating forests.…”
Section: Discussionmentioning
confidence: 99%
“…The suprapellis and subpellis are also thinner than the type material. However, the species can easily be recognized based on small to medium sized pileus with red colour, a smooth to purinose pileus surface, inamyloid suprahilar spots, basidiospore ornamentations that are composed of spines or warts connected by ne lines, and with hymenial cystidia and pileocystidia absent (Wisitrassameewong et al 2022). Russula bellissima is morphologically and phylogenetically closely related to the R. intervenosa reported from India and frequently grows in association with Shorea robusta dominating forests.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several Russula taxa in this study are supposed to be novel species. Recently, it was reported that six Thai Russula species (Wisitrassameewong et al 2022) and 17 Thai Lactarius species, which constitute 87% of this genus collected from the northern part of Thailand (Hyde et al 2018), were newly identified species.…”
Section: Diversity and Community Of Ecm Fungi In Dipterocarpus Alatusmentioning
confidence: 99%
“…In previous studies, about 161 species within subg. Heterophyllidiae were revealed around the world ( Ying, 1983 ; Li et al, 2013 , 2015 , 2018 , 2019 , 2021 ; Chen et al, 2014 , 2019 , 2021a , b , c , d ; Zhao et al, 2015 ; Zhang et al, 2017 ; Li and Deng, 2018 ; Song et al, 2018a , b , 2020 ; Wang et al, 2019 ; Yuan et al, 2019 ; Ghosh et al, 2020 ; Wisitrassameewong et al, 2020 , 2022 ; Vera et al, 2021 ; Altaf et al, 2022 ; Han et al, 2022 ; Song, 2022 ). Moreover, the edibility and poisonousness of the subgenus have also been noted, e.g., edible species, R. maguanensis J. Wang, X. H. Wang, Buyck and T. Bau, R. substriata J. Wang, X. H. Wang, Buyck and T. Bau, R. vesca Fr., and R. viridirubrolimbata J.…”
Section: Introductionmentioning
confidence: 99%